2019
DOI: 10.15835/nsb11210492
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climatic Factors on Radial Growth in Walnut (Juglans regia L.)

Abstract: Walnut is a species of high vigour, with relatively slow growth, and the size of trees grows with each year of growth. Accumulation of wood biomass, and respectively, productivity, is a resultant synthesis of physiological processes and interaction of trees with environmental factors. The authors have assessed growth characteristics of genotypes standing on their own roots in the sands area of Oltenia (Romania). In terms of tree height, it ranged from 8.53 m to 18.00 m, while trunk circumference varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Wang et al [29] evaluated Persian walnuts in China and selected six dwarf walnut rootstocks; 'Xinwen 609 , 'Xinwen 724 , 'Xinwen 908 , 'Xinwen 915 , 'Xin 916 , and 'Xinwen 917 as potential rootstocks for breeding. Analysis of growth traits of 'semi-cultivated' local genotypes of Juglans regia on their own roots, in the sands area of south-west Romania, showed that climatic and edaphic factors significantly influenced the annual growth ring width of the trees, but also their adaptability to environmental factors [33].…”
Section: Vigormentioning
confidence: 99%
“…Wang et al [29] evaluated Persian walnuts in China and selected six dwarf walnut rootstocks; 'Xinwen 609 , 'Xinwen 724 , 'Xinwen 908 , 'Xinwen 915 , 'Xin 916 , and 'Xinwen 917 as potential rootstocks for breeding. Analysis of growth traits of 'semi-cultivated' local genotypes of Juglans regia on their own roots, in the sands area of south-west Romania, showed that climatic and edaphic factors significantly influenced the annual growth ring width of the trees, but also their adaptability to environmental factors [33].…”
Section: Vigormentioning
confidence: 99%
“…Wang et al [29] evaluated Persian walnuts in China and selected six dwarf walnut rootstocks; 'Xinwen 609', 'Xinwen 724', 'Xinwen 908', 'Xinwen 915', 'Xin 916', and 'Xinwen 917' as potential rootstocks for breeding. Analysis of growth traits of 'semi-cultivated' local genotypes of Juglans regia on their own roots, in the sands area of south-west of Romania, showed that climatic and edaphic factors significantly influenced the annual growth ring width of the trees, but also their adaptability to environmental factors [33].…”
Section: Vigormentioning
confidence: 99%
“…Consequently, areas where frosts often occur after the blooming of fruit buds, leading to their freezing, are considered unsuitable for industrial cultivation of fruit crops, including walnuts [3][4][5][6]. For this reason, freezing is often an important selection criterion in breeding programs, and in a number of research programs, the main emphasis is placed on breeding varieties that are resistant to low temperatures [5,[7][8]. Low temperatures for walnuts are the main limiting factor that can explain the spread of species in cold climates [9][10].…”
Section: Introductionmentioning
confidence: 99%